Lobomycosis - Talhari, Sinésio; Talhari, Carolina (Clinics in dermatology, 2012)
Lobomycosis is a rare chronic fungal infection of the subcutaneous tissue found in South America, mainly in Brazil. It is caused by Lacazia loboi. Its clinical manifestations are dermal nodules, either lenticular or in plaques, and keloidlike lesions that can resemble nodular leprosy or leishmaniasis, other subcutaneous mycoses (sporotrychosis, chromomycosis, paracoccidioidomycosis), keloids, and malignant tumors. Diagnosis is made by the histopathological findings of the fungus. For treatment, surgical removal of the lesions, followed by itraconazole and clofazimine for disseminated lesions, has been used with variable results.